The interactional effect of omega-3 supplement and aerobic training on the Chemerin, CRP and TNFa levels in obese inactive women - طیبه محمدی خو; خسرو ابراهیم; حجت اله نیک بخت (Shahid Beheshti University, 2013)
Purpose: The aim of this study was to examine the interactional effect of omega-3 supplement and progressive aerobic training on the Chemerin, C reactive protein (CRP) and tumor necrosis factor alpha (TNFα) levels in obese inactive women. Methods: In this semi-exprimental study, 32 obese inactive women (age 36 ± 3 yr, body mass index 35.52± 5.23 kg/m3) who had no regular physical activity were selected as the subjects and randomly divided into four groups of 8: training (T), training - omega (T-OM), omega (OM) and control (C). The subjects in group T and T-OM were performed progressive aerobic training at an intensity corresponding to 60% to 80% of the subjects' maximum heart rate for 3 d/wk and for 12 weeks. The subjects in group T-OM and OM every week 7 omega-3 capsules, each containing 1000 mg omega-3 and subjects in group T and C were taking placebo during the same period. Fasting blood samples were taken before and after 12 weeks of aerobic training and Supplementation. Results of two-way ANOVA demonstrated the interactional effect of exercise - omega on the levels chemerin, CRP and TNF-a are significant (as follows: P-0/010, P-0/002, P-0/025) and the combined intervention of exercise - omega leads to further reduction of these variables compared with the effect of exercise and omega separately in obese women. Conclusion: progressive aerobic training combined omega-3 supplementation may ;with decrease fat mass and inhibiting the production of inflammatory processes upstream Including reduced macrophage infiltration; leading to a further Reduction of chemerin, CRP and TNF-α in Obese inactive women.